2021
DOI: 10.1109/jiot.2021.3056185
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic-Fusion-Based Federated Learning for COVID-19 Detection

Abstract: Medical diagnostic image analysis (e.g., CT scan or X-Ray) using machine learning is an efficient and accurate way to detect COVID-19 infections. However, the sharing of diagnostic images across medical institutions is usually prohibited due to patients' privacy concerns. This causes the issue of insufficient datasets for training the image classification model. Federated learning is an emerging privacy-preserving machine learning paradigm that produces an unbiased global model based on the received local mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
139
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 240 publications
(139 citation statements)
references
References 27 publications
0
139
0
Order By: Relevance
“…Most patients have an air bronchogram 60 . The distribution characteristics of the abnormalities on X‐ray images about these five types of pneumonia are similar to those of CT images (slices) 52,61‐73 . Although the collected 2D data (e.g., X‐ray images) in our proposed data set misses lots of information (original intensity level, spacing, etc.)…”
Section: Proposed Covid‐19 Pneumonia Data Setmentioning
confidence: 75%
“…Most patients have an air bronchogram 60 . The distribution characteristics of the abnormalities on X‐ray images about these five types of pneumonia are similar to those of CT images (slices) 52,61‐73 . Although the collected 2D data (e.g., X‐ray images) in our proposed data set misses lots of information (original intensity level, spacing, etc.)…”
Section: Proposed Covid‐19 Pneumonia Data Setmentioning
confidence: 75%
“…Four state-of-the-art CNN models, e.g., MobileNet, ResNet18, MoblieNet and COVID-Net, are used in the federated setting for evaluation, where ResNet18 is proven with the best COVID-19 detection performance (98.06%) in federated X-ray image learning settings. Moreover, a dynamic fusion-based FL method is proposed in [138] for CT scan image analysis to diagnose COVID-19 infections via two stages, including client participation and client selection. First, each client such as a medical institution make a decision to participate in the FL round based on the performance of the newly trained model.…”
Section: F Federated Ai For Privacy-aware Covid-19 Data Analyticsmentioning
confidence: 99%
“…Weishan Zhang et al [ 4 ] proposed a novel dynamic fusion-based federated learning approach to enhance federated learning model performance metrics. They found that all the recent studies on federated learning used the default federated learning settings which may introduce huge communication overhead and underperforms when there is data heterogeneity between clients.…”
Section: Related Workmentioning
confidence: 99%
“…The concept of federated learning was proposed by Google in 2016 as a new machine learning paradigm. The objective of federated learning is to build a machine learning model based on distributed datasets without sharing raw data while preserving data privacy [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation